Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10596-012-9336-9
|View full text |Cite
|
Sign up to set email alerts
|

An empirical theory for gravitationally unstable flow in porous media

Abstract: In this paper, we follow a similar procedure as proposed by Koval (SPE J 3(2): [145][146][147][148][149][150][151][152][153][154] 1963) to analytically model CO 2 transfer between the overriding carbon dioxide layer and the brine layer below it. We show that a very thin diffusive layer on top separates the interface from a gravitationally unstable convective flow layer below it. Flow in the gravitationally unstable layer is described by the theory of Koval, a theory that is widely used and which describes mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…While all the above studies replicate the classical scaling, only two numerical studies have reported a sublinear scaling: Farajzadeh et al [32] obtained Sh ≈ 0.0794Ra 0.832 , though for a relatively limited range of Ra (10 3 -8 × 10 3 ) using a constant-concentration boundary and a linear density-concentration profile; Neufeld et al [28] numerically determined Sh ≈ 0.12Ra 0.84 (also supported by experiments) for 2 × 10 3 Ra 6 × 10 5 but using a mixture of two miscible fluids involving in-terface movement and a non-monotonic density-concentration profile. Emami-Meybodi et al [36] concluded that the method of measuring the convective flux cannot be the source of different reported scaling behaviors.…”
Section: B Numerical Studiesmentioning
confidence: 82%
See 2 more Smart Citations
“…While all the above studies replicate the classical scaling, only two numerical studies have reported a sublinear scaling: Farajzadeh et al [32] obtained Sh ≈ 0.0794Ra 0.832 , though for a relatively limited range of Ra (10 3 -8 × 10 3 ) using a constant-concentration boundary and a linear density-concentration profile; Neufeld et al [28] numerically determined Sh ≈ 0.12Ra 0.84 (also supported by experiments) for 2 × 10 3 Ra 6 × 10 5 but using a mixture of two miscible fluids involving in-terface movement and a non-monotonic density-concentration profile. Emami-Meybodi et al [36] concluded that the method of measuring the convective flux cannot be the source of different reported scaling behaviors.…”
Section: B Numerical Studiesmentioning
confidence: 82%
“…Emami-Meybodi et al [36] concluded that the method of measuring the convective flux cannot be the source of different reported scaling behaviors. One could argue that the sublinear result of Farajzadeh et al [32] is due to the small parameter range of experiments, which includes less than one decade of Ra. Perhaps the combination of boundary set-up and densityconcentration profile shape determines the Sh-Ra scaling behavior, such that a constant-concentration BC with linear density-concentration profile results in linear scaling while an analogue two-layer fluid system with a nonmonotonic density profile results in sublinear scaling.…”
Section: B Numerical Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Fully resolved nonlinear simulations [21][22][23] demonstrate that the time for the onset of nonlinear effects depends on both the amplitude of initial perturbations and Ra, and is usually much greater than t o . Our characterization of linear instability as a function of viscosity contrast and various models would facilitate the study of the onset of nonlinear convection in such systems.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of research on fingering has already been done, both on viscous fingering (SaffmanTaylor instabilities) and instabilities caused by density differences; see, for example, Diersch and Kolditz (2002), Duijn et al (2004), Farajzadeh et al (2013), and Khosrokhavar et al (2014). There are several approaches.…”
Section: Introductionmentioning
confidence: 99%